Three New Species of Cosmetocleithrum (Monogenea: Dactylogyridae) Gill Parasites of Trachelyopterus galeatus (Siluriformes: Auchenipteridae) in Southeastern Brazil - de Oliveira Fadel Yamada, Priscilla [UNESP]; Yamada, Fabio Hideki; da Silva, Reinaldo José [UNESP] (Springer Nature, 2021)
Purpose: To describe three new species of Cosmetocleithrum in the gills of Trachelyopterus galeatus (Siluriformes, Auchenipteridae) from Aguapeí River, Upper Paraná River basin, São Paulo State, Brazil. Methods: Fifty-three specimens of T. galeatus were captured in the mouth of the Aguapeí River from August 2013 to June 2014. Monogeneans were mounted unstained in Hoyer’s and Gray and Wess’s medium. Results: Cosmetocleithrum spathulatum sp. n., Cosmetocleithrum baculum sp. n., and Cosmetocleithrum galeatum sp. n. differ from all known congeneric species mainly in the morphology of the accessory piece (i.e. spatulate-shaped, claviform, and a straight rod with hook-shaped distal portion, respectively). Also, the three new species share hooks with different sizes with hooks pairs 5 and 7 bigger than others and with an erect delicate point, inconspicuous thumb, longer shaft, and slender shank. Conclusions: To date, 18 species of Cosmetocleithrum were recognised parasitizing siluriforms in the Neotropical region. The present study expands the number to 21 species, however, despite this increase, the number of known taxa of monogeneans in neotropics is far from representing the ideal situation.
Keywords: Aguapeí River; Ancyrocephalinae; Catfishes; Neotropical region; Paraná River basin